Biofabrication Using Electrochemical Devices and Systems. Issue 4 (29th January 2020) - Ino, Kosuke; Ozawa, Fumisato; Dang, Ning; Hiramoto, Kaoru; Hino, Shodai; Akasaka, Rise; Nashimoto, Yuji; Shiku, Hitoshi
Abstract: Biofabrication is roughly defined as techniques producing complex 2D and 3D tissues and organs from raw materials such as living cells, matrices, biomaterials, and molecules. It is useful for tissue engineering, regenerative medicine, drug screening, and organs‐on‐a‐chip. Biofabrication could be carried out by microfluidic techniques, optical methods, microfabrication, 3D bioprinting, etc. Meanwhile, electrochemical devices and/or systems have also been reported. In this progress report, the recent advances in applying these devices/systems for biofabrication are summarized. After introducing the concept of biofabrication, biofabrication strategies using electrochemical approaches are summarized. Then, various electrochemical systems such as probes and chip devices are described. Next, the biofabrication of hydrogels for 3D cell culture, electrochemical modification on cell culture surfaces, electrodeposition of conductive materials in hydrogels for cell culture, and biofabrication of cell aggregates using dielectrophoresis is discussed. In addition, electrochemical stimulation methods such as electrotaxis are mentioned as promising techniques for biofabrication. Finally, future research directions in this field and the application prospects are highlighted. Abstract : This report summarizes the recent advances in applying electrochemical devices/systems for biofabrication. This report reviews the electrodeposition of hydrogels and conductive materials for 3D cell culture, electrochemical modification on cell culture surfaces, and cell aggregation using electrochemical devices, and electrochemical stimulation methods for biofabrication. Finally, this report highlights future research directions in this field and the application prospects.